Eksplorasi Etnomatematika Masyarakat Dayak Untuk Penguatan Pendidikan Kontekstual dan Ekonomi Berbasis Budaya: Ethnomathematics Exploration of the Dayak Community for Strengthening Contextual Education and Culture-Based Economy - Sudiansyah, Sudiansyah; Rostina, Rostina; Simin, Simin; Kurnianto, Dian; Heriyanto, Heriyanto (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to explore the ethnomathematical practices of the Dayak community in West Kalimantan and their potential for integration into education and local economic empowerment. The study is based on the view that mathematics exists not only in the classroom but is also embedded in everyday cultural activities. Using an explorative qualitative approach, data were collected through participatory observation, in-depth interviews, documentation studies, and literature reviews. The results indicate that in entrepreneurial activities, traditional crafts, and natural resource management, the Dayak community applies contextual mathematical principles such as ratios, geometric patterns, and ecological time calculations. This finding reinforces that local knowledge contains mathematical values that can be utilized as a contextual learning resource in schools. In conclusion, ethnomathematics serves not only as a bridge between culture and science but also as a strategy for sustainable education and economic development. This study recommends the development of ethnomathematics learning models, integration into the curriculum, and training for entrepreneurship, local culture-based industries, and sustainable natural resource management.